Urban wastewater treatment plants as hotspots for the release of antibiotics in the environment: a review - Michael, I. (2021)
Urban wastewater treatment plants (UWTPs) are among the main sources of antibiotics' release into various compartments of the environment worldwide. The aim of the present paper is to critically review the fate and removal of various antibiotics in wastewater treatment, focusing on different processes (i.e. biological processes, advanced treatment technologies and disinfection) in view of the current concerns related to the induction of toxic effects in aquatic and terrestrial organisms, and the occurrence of antibiotics that may promote the selection of antibiotic resistance genes and bacteria, as reported in the literature. Where available, estimations of the removal of antibiotics are provided along with the main treatment steps. The removal efficiency during wastewater treatment processes varies and is mainly dependent on a combination of antibiotics' physicochemical properties and the operating conditions of the treatment systems. As a result, the application of alternative techniques including membrane processes, activated carbon adsorption, advanced oxidation processes (AOPs), and combinations of them, which may lead to higher removals, may be necessary before the final disposal of the effluents or their reuse for irrigation or groundwater recharge.